Old and Grumpy but Still Game. Issue 5 (13th April 2017) - Vamplew, Wray
Abstract: My background as an economic historian has strongly influenced my approach to sports history which I practise as a combination of theory and empiricism, particularly of the quantitative kind. Theory is central to our understanding of the social science of sport and evidence makes the subject history rather than fiction. As sports historians we should emphasize that our discipline is as 'mainstream' as any other form of history and we can contribute to major historical debates on, for example, race, gender, identity, and nationalism.